Velopharyngeal stenosis, a late complication of radiotherapy - Lee, S.C; Tang, I.P; Singh, A.; Kumar, S.S; Singh, S. (Auris Nasus Larynx, 2009)
Choanal stenosis has recently been recognized as a late complication of radiation therapy for nasopharyngeal carcinoma. The management of velopharyngeal stenosis is challenging with high risk of restenosis. We report a case of velopharyngeal stenosis post-radiotherapy and illustrated the use of mitomycin-C to prevent restenosis. Mitomycin-C application has being shown useful adjunct to surgical technique in managing nasopharyngeal stenosis for surgeons.